Comparative Study of Neonatal Mortality Rate in Pelvic Colostomy for Arm under General Anesthesia and Local Anesthesia - Hasina, Kaniz; Ali, Md. Ansar; Yusuf, Md. Abdullah; Khan, Jaglul Gaffer; Talukder, Abdur Rabban; Rahman, Md. Khalilur; Sharif, Ahmad Raihan; Ahsan, Ali Imam (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 18-20 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12055